Growth and survival rate of endemic trees of Ethiopia: Olea africana and Hagenia abysinicca in the degraded lake of Haramaya Watershed, Ethiopia - Eba Muluneh Sorecha (Brawijaya University, 2017)
The study was conducted to explore the growth and survival rate of the native tree species of Ethiopia, Olea africana and Hagenia abysinicca in the degraded Lake Haramaya Watershed, eastern Ethiopia. Three sub watersheds of Lake Haramaya Watershed, namely: Bachake, Damota, and Tinike were selected purposefully on the basis of their extreme degradation and nearby vanished Lake Haramaya. In each sub watersheds, a total of about 12 main standard quadrats have been applied and the required data has been recorded. The result of the study indicated that Olea africana performs well at Damota sub watershed, accounting 38% of survival rate followed by Tinike sub watershed having a survival rate of 37%. Only 29% of the total planted Olea africana were survived at Bachake sub watershed. Furthermore, it has been revealed via this study that about 55.6% of Hagenia abysinicca were survived at Damota sub watershed. Comparing the survival rate of the two species, Hagenia abysinicca were better withstand and grow under an extreme pressure of local peoples intervention at all sub watersheds. Therefore, the study indicated that growing and maintaining of these two endemic trees in all sub watersheds were difficult task unless much awareness will be made at grass root level. Lastly, the study encourages mega projects on growth and survival rate of other native trees species in the degraded areas of Ethiopia.